Tipologi Nasabah dan Perspektif Emik Terhadap Bank Syariah: Sebuah Pendekatan Konstruktivisme - Anggraini, Nori; Sholihin, Muhammad (Sekolah Tinggi Agama Islam Negeri Curup, 2016)
The research uses the qualitative approach. It is applied the constructivism paradigm. Based on data, it can be summaries that society mada a decision to be a consumer of Islamic Bank because of the external factors. These factors, then, a main element which constructs the emic perspective, oftenly. It is foundation to conclude the consumers pattern of islamic bank. The study shows various type of consumers such as the followers-functional and excited; functional, and symphaty and functional. Keywords : Emic Perspective, Typology of islamic bank consumers, constructivism, islamic bank, and Paradigm